Revisiting the impact of corporate carbon management strategies on corporate financial performance: A systematic literature review - Maruli Sitompul; Arif Imam Suroso; Ujang Sumarwan; Nimmi Zulbainarni (Economies, 2023)
The objective of this research is to examine the relationship between carbon management strategies in corporations and their impact on financial performance. We employ a systematic literature review to analyze 223 articles retrieved from reputable journals indexed in Scopus. A total of 22 empirical studies covering various industry sectors and countries were selected and included in our analysis. The result indicates that 59% of the articles demonstrate positive findings. Among these, 50% show a significant positive impact, while 9% exhibit mixed results with both positive and negative outcomes in the short and long-term perspectives. These findings suggest that adopting carbon management strategies predominantly has a positive influence on corporate financial performance. In this study, we also provide a summary of the dependent, independent, and control variables, as well as commonly used indicators in this research topic, to help guide future quantitative research. Lastly, we offer a summary of the motivations, drivers, and barriers that corporations experience when implementing carbon management strategies. These insights will be valuable for business managers and policymakers, aiding them in successfully embarking on the journey to achieve net-zero emissions.
Keywords: 330; GHG emissions; climate change strategies; corporate carbon strategies; carbon management; carbon performance; financial performance